Preparation of graphene nanoplate added zinc-rich epoxy coatings for enhanced sacrificial anode-based corrosion protection. (October 2019) - Cao, Xiangkang; Huang, Feng; Huang, Chen; Liu, Jing; Cheng, Y. Frank
Highlights: Graphene nanoplate added zinc-rich epoxy composite coatings were prepared. The sacrificial anode-based corrosion protection is attributed to the Zn–GNP–Zn network. The barrier effect of the coating on water uptake is enhanced by the addition of graphene nanoplates. The delamination resistance of the coating is increased by graphene nanoplate addition. Abstract: In this work, graphene nanoplate (GNP) added zinc-rich epoxy (ZRE) composite coatings were prepared. Electrochemical measurements, surface characterization and galvanic corrosion testing were conducted to investigate the GNP-enhanced zinc (Zn) sacrificial anode-based corrosion protection of the coatings. The dispersed GNP serves as electronic channels to connect Zn particles to form a homogeneous Zn–GNP–Zn network in the coating matrix, resulting in an enhanced Zn sacrificial anode-based corrosion protection. The role of GNP in improved coating performance depends on Zn content in the coating. The prepared GNP-ZRE composite coatings also possess an enhanced delamination resistance.